2016
DOI: 10.1007/s11095-016-2071-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of the Anti-Tumor Effect of Sunitinib Combined with Dopamine in the Human Non-Small Cell Lung Cancer Xenograft

Abstract: The synergistic effect of sunitinib and dopamine was demonstrated by the preclinical experiment and confirmed by the developed PK/PD model. In addition, the regimens were optimized by means of modeling as well as simulation, which may be conducive to clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Tumor growth dynamics of two cell lines of breast cancer (HER2+ and Triple Negative) were modelled in the absence (unperturbed) or presence (perturbed) of MBQ-167 using the model proposed by Simeoni et al [ 10 ]. There is vast scientific evidence regarding the ability of the model to quantitatively characterize the time-course of tumor dynamics in xenograft experiments and evaluate the efficacy of anticancer drugs early in discovery and development [ 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The mathematical framework allowed for an adequate prediction of the tumor dynamics under the different groups considered.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth dynamics of two cell lines of breast cancer (HER2+ and Triple Negative) were modelled in the absence (unperturbed) or presence (perturbed) of MBQ-167 using the model proposed by Simeoni et al [ 10 ]. There is vast scientific evidence regarding the ability of the model to quantitatively characterize the time-course of tumor dynamics in xenograft experiments and evaluate the efficacy of anticancer drugs early in discovery and development [ 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The mathematical framework allowed for an adequate prediction of the tumor dynamics under the different groups considered.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [22] have found that dopamine (DA) may have the function inhibiting the growth of BCSCs characterized by CD44 + / CD24 −/low via the activation of D1 DA receptor, thus enhancing the response of SUN in breast cancer MCF-7/ADR. The combination therapy of SUN and DA was afterwards experimented on A549 non-small-cell lung cancer xenograft model, resulting in stronger response than SUN monotherapy [23]. These findings provide a potential solution that AX co-administered with DA could hopefully overcome the unsatisfactory outcome of AX as a single agent.…”
Section: Introductionmentioning
confidence: 94%
“…For example, studies have revealed that AX is primarily cleared via metabolism by CYP3A4, which is one kind of phase I metabolic enzymes, in human bodies [33,34]. While the small polar compound DA is metabolized by phase II metabolic enzymes, which are monoamine oxidase and catechol-O-methyl transferase [23]. Neither of them has been reported to impact the activity of the enzymes above.…”
Section: Pk-pd Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, we evaluated the in vitro inhibitory effect of a novel multikinase inhibitor, namely R8 (Figure 1 ), on several different types cancer cells. We further focused on the mechanism for its inhibition on lung cancer cells specifically, which showed distinct characteristics compared to Sunitinib, a clinically available MKI which has been investigated extensively in many types of cancer including lung cancer, either used alone or in combination with other therapeutics [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%